A SHAPE-SHIFTING CREATURE DISSECTED: POLITICAL REPRESENTATIONS OF JEAN MONNET IN EUROPEAN STUDIES - Pūras, Adomas (Baltic Journal of Political Science, 2015)
In this paper, I argue that contemporary political and intellectual conflicts over the right course for European integration are reflected in the historiography of Jean Monnet, the so-called founding father of the European Union (EU). Multiple and mutually antithetical representations of Monnet are explored across the central themes of the contemporary European debate: nationalism, sovereignty, political methodology, and economic ideology. I investigate how the different faces of Monnet are constructed and used to legitimate contradictory scholarly standpoints regarding these central themes. Along the way, I attempt to decipher the puzzle of Monnet’s elevation to the status of a theoretical pioneer in EU Studies. Finally, I also explore how different roles assigned to Monnet in the various narratives of the EU’s origins contribute to the construction of European identity.